FAMILY VALUES AMONG YOUNG PEOPLE IN SERBIA - Manić, Ivana S (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2016)
The theme of this work is the value orientations and family values of young people in Serbia, and discuss the results of some sociological studies and research on the established polarization of family values ​​among young people, that is, the existence of young people who adopt modern family values ​​and opposite to the those who still remain faithful to traditional family values. The main objectives of the research concerning the main factors that led to the  polarization and some of them are: the impact of social processes,  the impact of socio-economic status young people and material standard of their family, the influence of the educational level of young people, their parents and their family cultural capital and the influence of religion and the church.
Keywords: polarisation; analysis of value; traditional values; young people in Serbia; family value